Neo-Industrialization of Russian Economy as a Source of Social Well-Being Growth; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Klemasheva E. I. Elena Igorevna (2016, 2016)
Title screen